The co-benefit of emission reduction efficiency of energy, CO2and atmospheric pollutants in China under the carbon neutrality target - Fang-rong Ren; Zhe Cui; Xue Ding; Xue-rong Zhang; Rui-han Li; Qin Yao; Xiao-yan Liu (Energy Strategy Reviews, 2023)
The Yangtze River Economic Belt (YEB) and the Yellow River Ecological Economic Belt (YREB) surround the two biggest inland rivers and emit the greatest amount of carbon emissions in China. In order to implement China's dual carbon goal, this research applies a Meta-frontier DN-DEA model, including the carbon reduction factor (CRF), to assess the emission efficiency of energy, CO2, and atmospheric pollutants for a total of 19 regions in YEB and YREB from 2011 to 2017. The Synergistic climate risk control efficiency of atmospheric pollutants in the two economic belts are verified by tests for CO2 and three kinds of atmospheric pollutant emission elasticity coefficient and Kendall's coordination coefficient. The results are as follows: First, the overall efficiencies of the two economic belts are both improved by more than 30% when subject to CRF. YREB has great potential for carbon emission reduction, and the growth rate of its overall efficiency is higher than that of YEB. Second, YEB's input term efficiency performs better under the CRF constraint and has balanced development, while YREB's environmental pollution control input is insufficient. Third, the emission efficiencies of CO2 and atmospheric pollutants are significantly improved in YEB, while the environmental regulation of YREB is not obvious for the climate co-benefit of CO2 and atmospheric pollutants. Lastly, high level of climate co-benefit has revealed in YEB during 2011–2016, while in 2017, it plummets sharply. Conversely, YREB maintains a stable climate co-benefit.